Super-Speciality in India: A Boon or Bane? - Shivanee Kumari; BSC Reddy; Yogendra Malik; Suresh B. Math (Wolters Kluwer Medknow Publications, 2024)
In the past few decades, super-specialization has gained popularity in many medical disciplines. It provides professionals with a sturdy platform for advanced research and helps to deliver focused and extensive care in the fields of trauma and critical care, which can translate into good clinical outcomes for patients. Although this drift may bring about novel research opportunities, it may limit the number of doctors attending to the basic healthcare needs of the population. India is still struggling to provide primary healthcare services to its population. Super-specialization is a highly technology-driven industry, the costs of which our public health system cannot endure in the present settings. The current demand in India, where basic priorities are yet to be met, is to increase health awareness, provide basic healthcare facilities, and generate interest among medical professionals in providing general health services, especially in rural areas.